Socioeconomic status and educational inequality: digital competency pathways to creative problem-solving and academic performance - Liu, Jinglu; Chen, Yuwei (Frontiers in Psychology, 2026)
IntroductionThe digital divide extends beyond technology access to create educational inequalities through differential competency development, where socioeconomic advantages enable sustained digital engagement that enhances creative problem-solving. Grounded in social cognitive theory and digital divide frameworks, this study examines how socioeconomic status (SES) influences student outcomes through competency-mediated pathways that enhance creative problem-solving and academic performance.MethodsTwo studies in China examined competency pathways using structural equation modeling. Study 1 analyzed PISA data (N = 16,148) measuring SES, digital use, digital competency, and creative problem-solving. Study 2 (N = 558) additionally assessed academic ranking.ResultsHigher SES influenced digital use, which further led to digital competency, ultimately enhancing creative problem-solving. Additionally, digital use affected both academic ranking and creative problem-solving, while digital competency selectively enhanced creative problem-solving only, suggesting traditional academic assessments may not capture the strategic skills that constitute digital competency.DiscussionFindings demonstrate how SES-based resource disparities create differential competency acquisition in digital learning environments, providing cumulative advantages in creative problem-solving. This dual-pathway model supports social cognitive theory by showing how SES shapes competency development through digital use behaviors, while advancing digital divide theory through sequential mechanisms across multiple levels. These findings provide practical guidance for educational institutions to collaborate with parents in designing programs that foster digital competency development through sustained technology engagement for higher-order cognitive outcomes.